Effect of Air Preheating on the NOx Emissions and Reaction Kinetics of Ammonia/Methane Flames under Different Fuel Injection Strategies - Siqi Wang; Cheng Tung Chong; Meng-Choung Chiong (Chemical Engineering Transactions)
With the rapid advancement of industrialization, the escalating demand for energy and need for decarbonization prompt for the development of alternative renewable energy sources and highly efficient, clean combustion technologies. Ammonia, being a carbon-free fuel and an excellent hydrogen carrier has gained widespread attention. However, challenges persist in using ammonia as a fuel include high NOx pollutant emissions and the weak reactivity of ammonia. In this study, a swirl experimental platform was employed to investigate the effect of main air preheating on the flame and NOx emissions characteristics of ammonia-methane. Two fuel injection strategies were compared, i.e., dual-fuel injection and premixed injection mode, to form a dual flame and fully premixed swirl flame. The chemiluminescence experiments were performed to analyse the intensities of OH* emissions from flame. Numerical simulations were carried out using the chemical reaction network model. Results shows that both type of flames exhibit different flame structure, with dual flame exhibit higher OH* chemiluminescence intensities. Comparing fully premixed combustion with dual flame combustion modes at T = 473 K and ? = 0.6, the latter shows an 80 % reduction in NO emissions. For CO emissions, both modes maintain CO emissions within 10 ppm/kW, indicating high combustion efficiency. The simulation result shows that a significant increase in the percentage of NNH generated through the reaction of NO and NH2 in the NO reduction process within the dual flame, leading to a notable reduction in NOx emissions. In addition, a fraction of NH2 undergoes thermal decomposition, resulting in the formation of NH, but a portion of this process diminishes as the preheated air temperature rises.